2014
DOI: 10.1016/j.fct.2014.09.017
|View full text |Cite
|
Sign up to set email alerts
|

A toxicological safety assessment of a standardized extract of Sceletium tortuosum (Zembrin®) in rats

Abstract: A well-characterized standardized hydroethanolic extract of a traditionally recognized mak (mild) variety of Sceletium tortuosum, a South African plant with a long history of traditional ingestion, is marketed under the trade name Zembrin(®) as an ingredient for use in functional foods and dietary supplements. It is standardized to contain 0.35-0.45% total alkaloids (mesembrenone and mesembrenol ≥60%, and mesembrine <20%). A 14-day repeated oral toxicity study was conducted at 0, 250, 750, 2500, and 5000 mg/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 7 publications
(8 reference statements)
3
17
0
Order By: Relevance
“…To add up on the bioactive potential of the plant, the flavonoids were screened for their cytotoxicity against three cancerous cell lines and our results are in consonance with those obtained for compounds of Acanthus hirsutus Boiss (11.17-700 µg/ml), Euphorbia hirta (625 µg/ml) [52,53] and some naturally occurring quinones [54] . These results are in consonance with other studies where plant extracts were found to be non toxic [12,[16][17][18].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…To add up on the bioactive potential of the plant, the flavonoids were screened for their cytotoxicity against three cancerous cell lines and our results are in consonance with those obtained for compounds of Acanthus hirsutus Boiss (11.17-700 µg/ml), Euphorbia hirta (625 µg/ml) [52,53] and some naturally occurring quinones [54] . These results are in consonance with other studies where plant extracts were found to be non toxic [12,[16][17][18].…”
Section: Discussionsupporting
confidence: 92%
“…Since the potential of its aqueous extract has been reported earlier in Sood et al [15], the present study has thus been further extended to evaluate the best organic solvent and hence the major groups of bioactive phytoconstituents. The organic extract and active phytoconstituents have been tested for their various bioactivities such as antimicrobial single dose (5000 mg/ kg)] has also been determined by acute oral toxicity test using Swiss albino mice (males and females) weighing between 25 g to 35 g and aged 8 to 10 weeks [12,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…e studies herein described were conducted in compliance with OECD Principles of Good Laboratory Practice (GLP) [6], except for the following deviation: analytical control of the test item formulations for homogeneity and stability was not performed because no appropriate test method has been validated. We have described the OECD methods and laboratory standard operating procedures (SOP) used in previous works [7][8][9][10][11][12], and summarize them again, in brief, below.…”
Section: Test Itemmentioning
confidence: 99%
“…Extract Sceletium tortuosum (Zembrin ® ) has been shown to be safe and well tolerated in pre-clinical [6] and clinical studies [7]. The acute effects of extract Sceletium tortuosum (Zembrin ® ) administration in 16 healthy young adults was studied in a pharmaco-fMRI study focused on anxiety-related activity in the amygdala and its connected neuro-circuitry.…”
Section: Clinical Studiesmentioning
confidence: 99%